Alternative splicing in prostate cancer - Paschalis, Alec; Sharp, Adam; Welti, Jonathan C; Neeb, Antje; Raj, Ganesh V; Luo, Jun; Plymate, Stephen R; de Bono, Johann S (Nature reviews. Clinical oncology, 2018)
Androgen receptor (AR) splice variants (AR-Vs) have been implicated in the development and progression of metastatic prostate cancer. AR-Vs are truncated isoforms of the AR, a subset of which lack a ligand-binding domain and remain constitutively active in the absence of circulating androgens, thus promoting cancer cell proliferation. Consequently, AR-Vs have been proposed to contribute not only to resistance to anti-androgen therapies but also to resistance to radiotherapy in patients receiving combination therapy by promoting DNA repair. AR-Vs, such as AR-V7, have been associated with unfavourable clinical outcomes in patients; however, attempts to specifically inhibit or prevent the formation of AR-Vs have, to date, been unsuccessful. Thus, novel therapeutic strategies are desperately needed to address the oncogenic effects of AR-Vs, which can drive lethal forms of prostate cancer. Disruption of alternative splicing through modulation of the spliceosome is one such potential therapeutic avenue; however, our understanding of the biology of the spliceosome and how it contributes to prostate cancer remains incomplete, as reflected in the dearth of spliceosome-targeted therapeutic agents. In this Review, the authors outline the current understanding of the role of the spliceosome in the progression of prostate cancer and explore the therapeutic utility of manipulating alternative splicing to improve patient care.